Analysis of Current Scientific News According to Toulmin Argument Model and Determination of Students' Argument Levels - Hanne Türk; Munise Seçkin Kapucu (Anı Publishing, 2019)
This study aims to examine current scientific news about "Solar System and Beyond" unit, attracting the interest of 7th grade students and to determine students' argument levels. The study used qualitative research approach, 12 students from 7th grade of a secondary school in Kütahya have participated in the research during the spring term of 2017-2018 academic year. This study consisted of two stages and lasted two weeks. Data collection tools were scientific news that students brought to the classroom and "Argumentation Based Science Learning Student Template". Content analysis was used in the analysis of scientific news. Students' argument level was determined using 'Argumentation Evaluation Scale'. The results revealed an increase in the argumentation level of the students after the instruction of the science course in an argumentation-based way. According to the results, it is recommended that teachers carry argumentation-based activities to their classroom environment by using written and visual media.